Improvement of the training process of qualified female athletes engaged in bodybuilding in the general preparatory stage of the preparatory period, taking into account the biological cycle - Viacheslav Mulyk; Yevheniia Dzhym; Viktor Dzhym (Kharkiv State Academy of Physical Culture, 2017)
Purpose: substantiation of the methodology of the training process of qualified female athletes engaged in bodybuilding in the general preparatory stage of the preparatory period, taking into account the biological cycle. Material & Methods: in the study participated 18 qualified female athletes engaged in bodybuilding, included in the Kharkov region team of bodybuilding. Results: comparative characteristic of the most frequently used methodology of the training process in bodybuilding are shows. An optimal methodology for qualified female athletes engaged in bodybuilding has been developed and justified, depending on the initial form of the athlete at the beginning of the general preparatory stage of the training. The dependence of the change in the body weight of female athletes from the training process is shows. Conclusion: on the basis of the study, the author suggests an optimal training methodology depending on the mesocycle of training in the preparatory period in the general preparatory stage.